2010
DOI: 10.1016/j.carres.2009.11.013
|View full text |Cite
|
Sign up to set email alerts
|

A 3D-structural model of unsulfated chondroitin from high-field NMR: 4-sulfation has little effect on backbone conformation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
112
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(121 citation statements)
references
References 61 publications
9
112
0
Order By: Relevance
“…Our recent experimental observations 14 led to the hypothesis that two unsulfated chondroitin hexosamine hydroxyl hydrogen atoms (H-O4 and H-O6) are more solvent exposed in this carbohydrate backbone than in the hexosamine 4-epimerized hyaluronan backbone. Temperature coefficient experiments for chondroitin 14 and hyaluronan 66 have also shown the absence of persistent inter-residual hydrogen-bonding involving these atoms. The GLY-CAM06 RDF data illustrated in Figure 6 are consistent with these experimental observations and only GLYCAM06 (and to a lesser extent SCC-DFTB-D) could correctly predict hexosamine H-O4 to GlcA O5 hydrogen bond occupancies in Table 6.…”
Section: Intra-molecular Hydrogen Bonds and Solvent Interactionsmentioning
confidence: 92%
See 4 more Smart Citations
“…Our recent experimental observations 14 led to the hypothesis that two unsulfated chondroitin hexosamine hydroxyl hydrogen atoms (H-O4 and H-O6) are more solvent exposed in this carbohydrate backbone than in the hexosamine 4-epimerized hyaluronan backbone. Temperature coefficient experiments for chondroitin 14 and hyaluronan 66 have also shown the absence of persistent inter-residual hydrogen-bonding involving these atoms. The GLY-CAM06 RDF data illustrated in Figure 6 are consistent with these experimental observations and only GLYCAM06 (and to a lesser extent SCC-DFTB-D) could correctly predict hexosamine H-O4 to GlcA O5 hydrogen bond occupancies in Table 6.…”
Section: Intra-molecular Hydrogen Bonds and Solvent Interactionsmentioning
confidence: 92%
“…Figure 7C illustrates this graphically, further, the presence of non-4 C 1 chair geometries are consistent with the data in Figure 2C and the fact that this method did not reproduce the expected 4 C 1 hexapyranose puckering. Our recent NMR study also concluded that the effect of hexosamine 4-sulfation on the 3D-conformation of unsulfated chondroitin was small 14 ; the b(1?3) u I and w I torsions were found, respectively, to be 118 and 18 more positive in chondroitin-4-sulfate relative to unsulfated chondroitin. Using GLYCAM06, addition of 4-sulfate rendered both glycosidic torsions more positive in CS 2 relative to CN 2 , but to a larger degree than the experimental data (168 and 318 for u I and w I , respectively).…”
Section: Comparison Of Computed and Experimental Disaccharide Conformmentioning
confidence: 92%
See 3 more Smart Citations